New Hampshire Community Loan Fund : a nonprofit attempts to change the financial equation for manufactured homes - Oster, Sharon M.; Ford, Rachel Crocker; Earn, Joshua; Daffron, Jeffrey; Smith, Andrea Nagy ([London] : SAGE, 2016)
For Americans who cannot afford a standard home mortgage, one alternative to renting an apartment is to buy a mobile home. Also known as manufactured housing, mobile homes are built in a factory and then transported by tractor-trailer to the site where they will be occupied. They provide permanent housing at prices that are less than half the cost per square foot of regular 'site-built' houses. But although manufactured homes offer an affordable way to own a house, they also come with some special challenges. This case study discusses these challenges.
Originally Published in: Oster, S., Crocker Ford, R., Earn, J., Daffron, J., & Nagy Smith, A. (2010). New Hampshire Community Loan Fund: A Nonprofit Attempts to Change the Financial Equation for Manufactured Homes. 10-024. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; New Hampshire Community Loan Fund (Organization); Real estate investment -- United States -- Case studies; Strategic alliances (Business) -- Case studies; Nonprofit organizations -- Management -- Case studies